2021
DOI: 10.3389/fimmu.2021.728062
|View full text |Cite
|
Sign up to set email alerts
|

Development and Verification of the Hypoxia- and Immune-Associated Prognostic Signature for Pancreatic Ductal Adenocarcinoma

Abstract: We aim to construct a hypoxia- and immune-associated risk score model to predict the prognosis of patients with pancreatic ductal adenocarcinoma (PDAC). By unsupervised consensus clustering algorithms, we generate two different hypoxia clusters. Then, we screened out 682 hypoxia-associated and 528 immune-associated PDAC differentially expressed genes (DEGs) of PDAC using Pearson correlation analysis based on the Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression project (GTEx) dataset. Seven hypoxia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…This process was performed with 1,000 iterations by sampling 80% of all the data for each iteration to ensure clustering stability. The optimal clustering number was comprehensively determined by the item-consensus plots, the consensus heatmap, and the change in the area under the cumulative distribution function (CDF) curves, which was further confirmed by the proportion of ambiguous clustering (PAC) algorithm ( 28 , 29 ). Two hallmark-guided subtypes with distinct OS outcomes were recognized and visualized with principal component analysis (PCA) plots.…”
Section: Methodsmentioning
confidence: 90%
“…This process was performed with 1,000 iterations by sampling 80% of all the data for each iteration to ensure clustering stability. The optimal clustering number was comprehensively determined by the item-consensus plots, the consensus heatmap, and the change in the area under the cumulative distribution function (CDF) curves, which was further confirmed by the proportion of ambiguous clustering (PAC) algorithm ( 28 , 29 ). Two hallmark-guided subtypes with distinct OS outcomes were recognized and visualized with principal component analysis (PCA) plots.…”
Section: Methodsmentioning
confidence: 90%
“…Although its growth can be inhibited to a certain extent through energy metabolism, for some malignant solid tumors, hypoxia can stimulate tumor cell metabolism and changes in malignant behavior, providing a suitable environment for the survival of pancreatic cancer cells ( 33 ). Studies have shown that the hypoxic microenvironment is a key factor in tumor progression, immune escape, and treatment tolerance ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a comparable smaller AIC, the Lasso-Cox model outperformed the combination of Cox regression. Actually, Lasso-Cox was adopted in extensive research to determine prognostic molecular features or clinical characteristics [ 20 22 ]. For instance, the group Lasso-Cox model was executed to predict patient prognosis and identify risk protein complexes in glioblastoma multiforme, ovarian cancer, and lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%